Advances in neural networks – ISNN 2018 : 15th International Symposium on Neural Networks, ISNN 2018, Minsk, Belarus, June 25-28, 2018, Proceedings /: 15th International Symposium on Neural Networks, ISNN 2018, Minsk, Belarus, June 25-28, 2018, Proceedings. (2018) - Unknown
No abstract available